GRAMMATICAL ERRORS IN DESCRIPTIVE TEXT WRITTEN BY DIFFERENT GRADES OF SMP DHARMA PANCASILA MEDAN - Grace Seprima Pakpahan; Berlin Sibarani; Safrida Lubis (Universitas Negeri Medan, 2021)
GRAMMATICAL ERRORS IN DESCRIPTIVE TEXTWRITTEN BY DIFFERENT GRADES OF SMP DHARMAPANCASILA MEDAN*Grace Seprima Pakpahan**Prof. Dr. Berlin Sibarani, M.Pd** Safrida Lubis, S.Pd, M.HumABSTRACTThe study aims to analyze grammatical errors in descriptive text written bydifferent grades. This study was conducted by using descriptive qualitative design.The sources of this data are students in the eighth grade which consists of 21students and the ninth grade which consists of 20 at SMP Dharma PancasilaMedan. The data of the study were obtained from students’ descriptive text andinterview. The analysis found that the grammatical errors written by eighth gradeare subject verb agreement (46 cases), verb tense (7 cases), verb form (5 cases),singular/plural (2 cases), word form (11 cases) and sentence structure (26 cases),while the grammatical errors written by ninth grade are subject verb agreement(43 cases), verb tense (7 cases), verb form (4 cases), singular/plural (4 cases),word form (12 cases) and sentence structure (18 cases). From the analysis wasfound the factors underlying the grammatical error made by eighth grade areimperfect learning (4), overgeneralization (11) and influence of the nativelanguage (6), while the factors underlying the grammatical error made by ninthgrade are imperfect learning (8), overgeneralization (6) and influence of the nativelanguage (6).Key words : Grammatical errors, Descriptive text, Eighth and Ninth GradeStudents